Slide7.JPG

Slide8.JPG

 


Transcript

Ex 10.1, 2 Simplify and express the result in power notation with positive exponent. (iv) 〖(3〗^(−7)÷ 3^(−10)) × 3^(−5)〖(3〗^(−7)÷ 3^(−10)) × 3^(−5) = (𝟑^(−𝟕)/𝟑^(−𝟏𝟎) )× 3^(−5) = (𝟑^(−𝟕−(−𝟏𝟎) ) ) × 3^(−5) = (3^(−7 + 10) ) × 3^(−5) = 𝟑^𝟑 × 𝟑^(−𝟓) = 3^(3 + (−5) ) = 𝟑^(𝟑− 𝟓 ) = 3^(−2) = 𝟏/𝟑^𝟐

Go Ad-free
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 14 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.